2021
DOI: 10.31557/apjcp.2021.22.3.757
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy Negates the Effect of SDF1 mRNA to Distant Metastasis and Poor Overall Survival in Breast Cancer Patients

Abstract: III, while 26% have metastases (Yarso et al., 2012). One crucial component of metastasis is the axis stromal cell-derived factor 1α (SDF1a) with its receptor CXCR4 (Chemokine Motif Receptor 4). Some studies suggest

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…The mechanism of cytotoxic agents causing CIA was described by Luo et al through experiments in experimental animals (C57BL/6 mice) which found the role of inflammation regulation, SDF-1/CXCR4, and cellular apoptosis in the ovarian tissue that played a role in premature ovarian failure [25]. However, Yarso et al found that chemotherapy abolished the effects of SDF1a/CXCR4 in breast cancer patients [26]. This indicates that other factors play a role in the mechanism of ovarian damage due to chemotherapy through complex interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of cytotoxic agents causing CIA was described by Luo et al through experiments in experimental animals (C57BL/6 mice) which found the role of inflammation regulation, SDF-1/CXCR4, and cellular apoptosis in the ovarian tissue that played a role in premature ovarian failure [25]. However, Yarso et al found that chemotherapy abolished the effects of SDF1a/CXCR4 in breast cancer patients [26]. This indicates that other factors play a role in the mechanism of ovarian damage due to chemotherapy through complex interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is a common and debilitating disease that affects millions of women worldwide.1 It causes significant physical, emotional, and psychological challenges for those who are diagnosed. Patients with breast cancer frequently need breast reconstruction surgery [ 1 , 2 ]. Breast reconstruction is an important part of the overall treatment and recovery process of breast cancer because it aims to restore the form, shape, and symmetry of the breast following a mastectomy [ 1 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%